EVALUASI ADOPSI TEKNOLOGI BUDIDAYA DAN KELAYAKAN USAHATANI PADI DI PROVINSI SULAWESI SELATAN - Amar K Zakaria (Universitas Sebelas Maret, 2014)
Rice is the strategic commodity as the main foodstuff and the source of the income of most rural households. The application of cultivation technology played an important role towards the increase in the production and the productivity of lowland rice. Therefore, the application of the innovation of recommendation technology in the level of the farmer was the strategy in the increase program in the production of the national rice towards the continuous self-sufficiency. This research was carried out during 2012 in the Sidrap Regency and Luwu, Provinsi South Sulawesi with the survey method. The primary data was gathered through the interview to the respondent's 80 farmers with the questionnaire structure filling. The data was processed with cross tabulation and the level of the appropriateness of the farming was measured with Gross B/C the ratio and profitability. Results of the research showed that adoption of rice technology in the farmer level was adopted with technology recommendation. The analysis of benefit and cost to get gross B/C > 1, based on that the farming of lowland rice in the research territory gave the profit and economically appropriate was made an effort operation.